KAMPANYE POLITIK VICTORY-JOS MELALUI MEDIA SOSIAL PADA PEMILIHAN KEPALA DAERAH PROPINSI NUSA TENGGARA TIMUR TAHUN 2018 - Nyaleson Ndoda, Phlips Juniory; Yuningsih, Neneng Yani; Djuyandi, Yusa (Al-Ijtima`i: International Journal of Government and Social Science, 2020)
The current political campaign has developed taking advantage of technological developments. New campaign platforms are provided by technological sophistication that makes it easier for people to access social media, which is then used by political elites to maximize social media opportunities for campaigns. The electoral strategy is needed by every candidate participating in the general election, as well as by candidates for regional leaders who participate in the regional election campaign, including Victory-Joss, who participated in the 2018 NTT Pilgub Competition. must try to reach the entire NTT region, which is an island province, in order to introduce itself, to convey political messages to almost all NTT people so that they can become better known and all their best intentions for NTT can become known. This requires an expansion of Victory Joss campaign teams, social media as one of the Victory Joss campaign packages, to reach the broader community. The aim of this study is to find out and explain how Victory-Jos became politically active in the regional elections in the province of East Nusa Tenggara in 2018 via social media. As research, qualitative research is used. The data in this study was collected through interviewing techniques and document collection. The results showed that the campaign strategy through online media running on the Victory Joss package was to form a media team using social media as a media campaign for Victory Joss packages. This media team then went through the Agenda Setting, Framing, and Priming mechanisms to pack The focus of the Victory Joss package to be promoted on social media includes product orientation, candidate orientation, and ideology orientation, to promote positive public opinion on Victory-Jos to influence. Social Media Reached Victory-Jos's winning team consists of five social media commonly used by the community, namely Facebook: @ Victoryjoss4NTT, Twitter: @Victory_joss, Instagram: @Victory_joss, and Youtube: Victory-Joss.